Interleukin-6 urin sebagai pemeriksaan cepat pielonefritis pada neonatus - Nezman Nuri; Rafita Ramayati; Oke Rina Ramayani; Rosmayanti Syafriani Siregar; Beatrix Siregar (Fakultas Kedokteran USU, 2013)
Pyelonephritis is a common infection to all children in all age groups, including the newborn. The diagnosis of urinary tract infection is established certainly by urine culture. Additional investigations can be done to help confirm the diagnosis, such as urinary interleukin-6. Increased number of urinary interleukin-6 is helpful to quickly confirm the occurrence of pyelonephritis. Keyword : pyelonephritis; neonates; urine culture; interleukin-6